2017
DOI: 10.1016/j.psyneuen.2017.07.482
|View full text |Cite
|
Sign up to set email alerts
|

Childhood maltreatment is associated with increased risk of subclinical hypothyroidism in pregnancy

Abstract: The critical importance of thyroid hormones for fetal development is well established. The developing fetus is dependent on the mother for adequate thyroid hormone supply, and maternal thyroid dysfunction in pregnancy may result in suboptimal fetal development. Because exposure to childhood maltreatment (CM) has been associated with thyroid dysfunction in the non-pregnant state, we sought to test the hypothesis that exposure to CM may represent a risk factor for the development of maternal hypothyroidism in pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 51 publications
1
10
0
Order By: Relevance
“…Very few studies have investigated how HPT functioning in general may be altered as a result of adverse experiences during childhood. Most recently, Moog et al (2017) were able to demonstrate that women with moderate to severe childhood trauma had a significantly enhanced risk of subclinical hypothyroidism during pregnancy, as indicated by higher circulating levels of TSH. Another study found altered fT3 in women reporting a history of sexual abuse when compared to non-abused women ( Bunevicius et al, 2012 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Very few studies have investigated how HPT functioning in general may be altered as a result of adverse experiences during childhood. Most recently, Moog et al (2017) were able to demonstrate that women with moderate to severe childhood trauma had a significantly enhanced risk of subclinical hypothyroidism during pregnancy, as indicated by higher circulating levels of TSH. Another study found altered fT3 in women reporting a history of sexual abuse when compared to non-abused women ( Bunevicius et al, 2012 ).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, there is evidence to suggest that early life adversity can modulate HPT functioning. For instance, a recent study found higher TSH in pregnant women with versus without childhood trauma ( Moog et al, 2017 ). Similarly, altered circulating levels of fT3 were shown in women with childhood sexual abuse when compared to non-traumatized women, the direction of which depended on whether they had a menstrually related mood disorder or not ( Bunevicius et al, 2012 ).…”
Section: Introductionmentioning
confidence: 99%
“…In low- and high-income countries, women exposed to CM are at increased risk of developing postpartum depression [ 9 ], which in turn increases the risk of impaired maternal-child attachment [ 10 ] and depression in the child [ 11 ]. CM is also associated with increased risk of subclinical hypothyroidism in pregnancy [ 12 ]. Furthermore, potential associations between maternal exposure to CM, fetal brain development [ 13 ], brain anatomy [ 14 ], and obesity in the newborn [ 15 ] are well documented.…”
Section: Effects Of CM On Mental and Physical Healthmentioning
confidence: 99%
“…Childhood abuse leads to altered serum TSH and thyroid hormones levels. Early life trauma evaluated using CTQ is associated with reduced T3 levels, but not with altered peripheral T4 levels in adolescents (Machado et al, 2015), and increased TSH levels in women that experienced childhood trauma have also been found (Bunevicius, Leserman, & Girdler, 2012;Moog et al, 2017), suggesting enhanced risk of hypothyroidism. On the other hand, some distinct effects of childhood trauma have also been reported on HPT function in women with functional somatic syndrome (Fischer et al, 2018), and with post-traumatic stress disorder (Friedman, Wang, Jalowiec, McHugo, & McDonagh-Coyle, 2005), in which higher childhood trauma was associated with lower TSH.…”
Section: Early Life Stress Adversities and Feeding-related Behaviorsmentioning
confidence: 90%